Stalking - Amiky, Luciana Gerbovic (2014)
This dissertation addresses stalking, an ancient social phenomenon, little known and seldom studied in Brazil. The term, kept in English throughout this work for lack of equivalence in Portuguese, could be translated as "relentless persecution of" someone. The most frequent victims are women, and the action often derives from a relationship ended against the will of the one who will become the stalker. After discussing some concepts in stalking, built especially by jurists, physicians and psychologists, we will present the constitutive elements of the phenomenon, its categories and a brief history, also listing the framework of stalking under the laws of countries like the United States and European nations. The emphasis of this dissertation is on the Civil Law, which is why the criminal aspects of stalking will not be covered, even though they are basal to the prevention of the damage caused by the pursuer. Starting from the only two civil cases judged on stalking so far in the country, we will show how the stalker can be civilly liable based on Brazilian legal grounds, without the need for a specific antistalking civil law. We will then access the damage suffered by victims, which forms the basis for due compensation. Finally, we will discuss the principles of prevention and solidarity, as the damage caused by the practice of stalking is so onerous that effectively compensating the victim becomes an impossibility. Precisely because of the severity and growth of the phenomenon over the past few years is that we believe in the importance of the study of stalking by legal practitioners